Economic Analysis of The Contribution of Renewable Energy Sources to the Decarbonization of the Power Systems - Adel Ramadan Hussien Mohamed; Ali Ahmed, Abdssalam (African Journal of Advanced Pure and Applied Sciences, 2023)
The economic analysis of the contribution of Renewable Energy Sources (RESs) to the decarbonization of power systems involves evaluating the financial implications and overall benefits of transitioning towards cleaner energy sources. As traditional power systems heavily rely on fossil fuels, which contribute to Greenhouse Gas (GHG) emissions, the integration of RESs plays a crucial role in reducing carbon footprints and addressing Climate Change (CC). Economic analysis assesses the costs and benefits associated with the adoption of RESs in power systems. It involves considering factors such as the initial investment required for deploying renewable energy technologies, Operational and Maintenance (O&M) costs, potential revenue generation, and the long-term environmental benefits. This analysis enables policymakers, investors, and stakeholders to evaluate the financial viability of transitioning to cleaner energy systems.